INFLUENCE OF OPERATING COST, WORKING CAPITAL DAN PENDAPATAN TERHADAP LABA BERSIH PADA PERUSAHAAN INDEKS LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2012-2016 - Lilia, Wirda; Sinaga, Jemson; Puspita, Cindy; Simbolon, Fransiska (EDUTECH CONSULTANT, 2019)
This research was conducted to test and analyze the effect of Operating Costs, Working Capital and Revenue on Net Income on LQ45 companies listed on the Indonesia Stock Exchange in 2012-2016. The phenomenon of increasing Operational Costs, Working Capital and Income is not always followed by an increase in Net Profit. The approach used in this study is a quantitative approach, the type of research used is quantitative descriptive and the nature of this research is a causal relationship. The sampling method uses purposive sampling, with a sample of 35 companies. Data collection techniques use documentation study, quantitative data types and secondary data sources. The study used multiple linear regression analysis. The coefficient of determination is 98.4%, which means that 98.4% of Net Profit is able to explain Operating Costs, Working Capital and Revenue. Simultaneous test results show Operational Costs, Working Capital and Revenue have a significant effect on Net Profit. Partially Operational Costs have no significant effect on Net Profit. Working Capital and Income partially have a significant effect on Net Income.